Unravelling the role of mitochondrial TERT in a thyroid cancer cell line - Chantre, Ana Sofia Moreira (2023)
Besides its established canonical function as the catalytic subunit of telomerase involved in telomere elongation, there is increasing evidence that suggest that Telomerase Reverse Transcriptase (TERT) plays several other (non-canonical) celular functions. In particular, i tis known that TERT can translocate into mitochondria. However, the precise mitochondrial function(s) of TERT remains to be fully unravelled. In the contexto of thyroid cancer TC), TERT reactivation is often associated with worse prognostic features. However, the canonical functions of TERT alone are not enough to account for these clinical associations. Therefore, the main objective of this project was to unravel non-canonical roles of TERT, in particular within the contexto of mitochondria, by comprehensively characterizing TPC-1 thyroid cancer cells which have been genetically modified to disrupt TERT’s-N-terminal Mitochondrial Target Sequence (MTS), thus preventing its translocation into mitochondria. For this, two clones were chosen, clone “noMTS1” and “noMTS2”, both preserving the in-frame TERT sequence but with only clone “noMTS1” retaining telomerase activity. Our results from phase contract microscopy and PrestoBlue viability assay revealed that the growth rate of the clones was diferente from that of their Mock control counterpart and also that it changed throughout the passege of the cells. Clone “noMTS1” cells seemed to be larger and their growth became increasingly higher over-time in culture. Clone “noMTS2” cells, allthough initially showing similar morphology and growth patterns to that of Mock cells, their size increased over-time and these cells lost thei initial growth capacity. Fluorescence and transmission electron microscopy (TEM) analysis revealed increased heterogeneity in cell size (which tended to be larger), and a noticeable increase in nucleus size, in lone “noMTS1” and “noMTS2” cells, compared to Mock cells. TEM analysis further reealed that clone “noMTS1” cells had higher mitochondria number, and that both clone “noMTS1” and “noMTS2” presented mitophagy- and autophagy- associated features. Seahorse metabolic assay showed that clone “noMTS1” had increased oxygen consumption rates in response to FCCP, and a slight tendency for higher spare respiratory capacity and maximal respiration levels. Overall, our study on the characterization of genetically manipulated TPc-1 cells which prevented TERT’s translocation into mitochondri revealed relevant diferences regarding cell growth and survival, and celular, nuclear, and mitochondrial features of these cells, further supporting that mitochondrial TERT has a fundamental role in thyroid cancer cells physiology.